An exploratory study of final grades awarded to bachelor with honours and masters students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Bolger, Patricia (Massey University, 1990)
This study explores the final grades awarded to Bachelor with honours and Masters students in New Zealand universities from 1960 to 1989 as a function of students' gender, the university attended, the degree completed, and the subject studied. These grades were also compared with the grades awarded to Bachelor with honours students in England and Wales from 1974 to 1989. Chi-square test statistics were used to measure the significance of these relationships. In New Zealand women were awarded significantly more first class degrees than men. In England and Wales men were awarded significantly more first class degrees than women. Science students were awarded a higher percentage of first class degrees than other students in both New Zealand and England and Wales. In New Zealand Bachelor with honours students were awarded first class degrees more frequently than Masters students. Political and historical developments, the nature of the grading procedures used, and institutional and departmental variance provide partial explanation for some of the results. It is clear that no single factor is responsible for these variations in degree performance, but rather a complex interaction of several factors. It is concluded that in New Zealand and England and Wales, gender, university, the degree undertaken, and the subject studied, all have an effect on the final grade a student is awarded.
Keywords: Grading and marking (Students); New Zealand